Early occupational hearing loss of workers in a stone crushing industry: Our experience in a developing country. - Kitcher, E.; Ocansey, G.; Tumpi, D. (My University, 2012)
Noise-induced hearing loss (NIHL) is an irreversible sensorineural hearing loss associated with exposure to high levels of excessive noise. This paper aims to assess the prevalence of early NIHL and the awareness of the effects of noise on health among stone crushing industry workers. This was a comparative cross-sectional study in Ghana of 140 workers from the stone crushing industry compared with a control group of 150 health workers. The stone workers and controls were evaluated using a structured questionnaire, which assessed symptoms of hearing loss, tinnitus, knowledge on the health hazards associated with work in noisy environment and the use of hearing protective device. Pure tone audiometric assessment was carried out for stone workers and controls. Noise levels at the work stations of the stone workers and of the controls were measured. Statistical Analysis of data was carried out using SPSS package version 16. The mean age of stone workers and controls was 42.587.85 and 42.1912 years, respectively. Subjective hearing loss occurred in 21.5% of the workers and in 2.8% of the controls. Tinnitus occurred in 26.9% of stone workers and 21.5% of controls, while 87.5% stone workers had sound knowledge on the health hazards of a noisy environment. Early NIHL in the left ear occurred in 19.3% of the stone workers compared with 0.7% in controls and in the right ear, it occurred in 14.3% of the stone workers and in 1.3% of the controls; P<0.005. In conclusion, the prevalence rate of early NIHL among stone crushing workers is about 19.3% for the left ear and 14.3% for the right ear.
Keywords: EMTREE medical terms: adult; article; case control study; comparative study; cross-sectional study; developing country; female; Ghana; human; industrial noise; male; middle aged; mining; noise injury; occupational disease; occupational exposure; prevalence; protective equipment; pure tone audiometry; questionnaire; risk factor; tinnitus; utilization review MeSH: Adult; Audiometry, Pure-Tone; Case-Control Studies; Cross-Sectional Studies; Developing Countries; Ear Protective Devices; Extraction and Processing Industry; Female; Ghana; Hearing Loss, Noise-Induced; Humans; Male; Middle Aged; Noise, Occupational; Occupational Diseases; Occupational Exposure; Prevalence; Questionnaires; Risk Factors; Tinnitus Medline is the source for the MeSH terms of this document.